(untitled) (Journal of Mathematical Modeling and Fractional Calculus, 2025)
In order to estimate and control the recent corona virus disease 2019 outbreak, under me dia impact. Most countries impose stringent intervention measures to halt the spread of COVID-19. Globally, the COVID-19 epidemic has raised a lot of concerns. A non-smooth SIR system is proposed to investigate the impact of three control strategies (vaccination, therapy, and media coverage) on the spread of an infectious disease. Social media platforms like Face book, Twitter, and others have been crucial in spreading information during the COVID-19 outbreak, both factual and misleading, which has led to widespread confusion. When the susceptible population surpasses the threshold value, the traditional epidemic model comprises media coverage, linear functions that describe vaccine injection, and treatment tactics. COVID-19 model under media coverage investigated both qualitatively and quantitatively. models key proportion are also verified like boundedness, uniqueness and existence. Stability Analysis his also know development on local and global scale in order to properly manage funds and human resources and create successful disease preventive marketing efforts, organizations, institutions, enterprizes, policymakers, and educators who are in charge of infection and disease control must keep a close eye on infection rates.